Game-Based Learning Media to Improve Understanding of Whole Numbers and Length Measurement for Grade II Elementary School Students - Sri Febrina Dewi; Yamanto Isa; Leni Pebriantika (Indonesian Technology and Education Journal, 2026)
This research is driven by the low level of student activity and understanding in Mathematics at SD Negeri 14 OKU, where abstract concepts and conventional teaching methods often lead to boredom and confusion. The study aims to develop game-based learning media specifically for whole numbers and length measurement materials for Grade 2 students. The development follows the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) integrated with Tessmer’s formative evaluation. The media was developed using Wordwall as the primary platform, supported by Canva for visual design and Heyzine for interactive flipbooks. Validation results from experts indicated high feasibility: material experts (89.75%), instructional design experts (87.8%), and media experts (91.4%), all categorized as "Very Good". Furthermore, evaluation phases showed excellent results, with one-to-one evaluation reaching 90.07%, small group evaluation at 88.32%, and a field test involving 20 students yielding 89.26%. The final product, Prototype III, effectively creates a joyful learning environment that enhances student motivation and simplifies complex mathematical concepts. In conclusion, this game-based learning media is highly feasible and effective for use in elementary mathematics education to improve student engagement and learning outcomes.